Influency of one nutraceutic on semen, testosterone, cortisol, eritrogram and body weight in young bulls Bos taurus indicus - Chacur, Marcelo George Mungai; Aurélio, Paulo Tiago Ferreira; Oba, Eunice [UNESP]; Laposy, Cecília Braga; Scalon Jr., Orivaldo; Inague, Leandro; Do Nascimento Kronka, Sérgio [UNESP] (Universidade Estadual de Londrina, 2010)
The purpose of this study was to investigate the nutraceutic (Promater®) influence on semen, body weight, eritrogram and hormones testosterone and cortisol in Nelore young bulls. Twenty Nelore bulls were utilized, aging between 30 and 36 months, divided in group 1 (G1)=10 (control) and group 2 (G2)=10 (nutraceutic group-Promater®: 20 mL/animal/day, during 70 days). Corporal weight, blood samples to eritrogram, testosterone and cortisol were obtained in days zero (D0), 35 (D35) and 70 (D70) in two groups. There was difference (P<0.01) among days collected (0, 35 and 70) with means of 424.30 kg, 480.70 kg and 502.60 kg, respectively, but there was not difference between groups. There was not difference among groups to semen, eritrogram, cortisol (G1=3, 19 μg/dL; G2=2, 91 μg/dL) and testosterone (G1=274, 48 ng/dL; G2=509, 65 ng/dL). The results exposed allow concluding that were not observed significative effect of the nutraceutic upon evaluated parameters: body weight, semen, hormonal profile and eritrogram.
Influência de um nutracêutico no sêmen, testosterona, cortisol, eritrograma e peso corpóreo em touros jovens Bos taurus indicus
Keywords: Blood; Hormones; Nutrition; Semen; Zebu bull